Inverse Compton scattering x-ray source from laser electron accelerator in pure nitrogen with 15 TW laser pulses. (29th November 2018) - Zhu, Changqing; Wang, Jinguang; Feng, Jie; Li, Yifei; Li, Dazhang; Li, Minghua; He, Yuhang; Ma, Jinglong; Tan, Junhao; Zhang, Baolong; Yan, Wenchao; Chen, Liming
Abstract: Using 15 TW laser pulses, we present a systematic investigation on tabletop inverse Compton scattering (ICS) hard x-ray source based on the self-synchronized combination of laser-driven pure nitrogen plasma accelerator and plasma mirror (PM). In the scheme of pure nitrogen medium and ionization induced injection, the laser wake-field acceleration (LWFA) is performed at a lower laser intensity of a 0 ∼ 2 and a lower plasma density of n e ∼ 8 × 10 18 cm −3, which lead to the weak evolution of beam profile and high energy transmission rate of 95%. We found the quality of electron beam is insensitive to the focus position of the laser pulse near the tail of gas jet, so it becomes possible to place the focus close to the PM. Tunning the collision point of accelerated electron bunch and reflected laser beam to the optical focal spot, ICS is dramatically increased. Ultimately, the produced ICS x-rays have the yield of 4.5 × 10 7 . And the photon number exceeding 200 keV is about 1.2 × 10 7 . Demonstrated by our results, stable and high yield of x-ray source in hundreds of keV range could be achieved via all-optical ICS driven by only ten terawatt lasers. This reduces the threshold of obtaining high-energy femtosecond x-rays.